Erysiphe machilicola: a new powdery mildew species on Duthie’s Bay Tree - Zafar, Irsa; Afshan, Najam-Ul-Sehar; Khalid, Abdul Nasir; Götz, Monika (Phytotaxa, 2023)
A new species of Erysiphe infecting Duthie’s bay tree in Azad Jammu & Kashmir, Pakistan, is described and illustrated based on molecular and morphological analyses. Erysiphe machilicola sp. nov. is morphologically distinct from other Erysiphe species on hosts of the Lauraceae by having longer conidiophores, larger chasmothecia with longer appendages, above all, it is distinguished from E. machiliana, the only so far known Erysiphe species on Machilus, by lacking bristle-like appendages (remnant of anchor hyphae) and a different phylogenetic position, confirmed by sequence analyses of the type material of the latter species. The phylogenetic relationship of the new species to other closely related species is discussed based on ITS rDNA sequences, which phylogenetically supports its identity as a new species within the genus Erysiphe. A comprehensive description along with photographs and a phylogram showing its exact phylogenetic position and a comparison with closely related taxa is provided.